Chronicle and the epic: Machado de Assis in homeric verses - Ionara Satin; Daniela Mantarro Callipo (Semina: Ciências Sociais e Humanas, 2015)
The aim of this study is to show the presence of classical epic, Homer's Iliad, in the chronicle of Machado de Assis, analyzing the intertextual dialogue between Machado de Assis and the epic poem by Homer, considering the concept of intertextuality developed by Julia Kristeva from philosophical conceptions of Bakhtin. In the chronicle of March 18, 1894 for the newspaper Gazeta de Notícias on sunday column "A Semana", Machado de Assis crosses Homer's epic to his chronicle, rewrites the epic text for the daily issues of his weekly column. To Tiphaine Samoyault, writing is rewriting, "stand on the existing foundations and contribute to a continued creation" (2008, p. 77) one of the principles of intertextuality. It was observed that from the reading and assimilation of the classic poem, Machado de Assis can approach so far genres, bringing the verses to his prose, leaving it closer to poetry. In this sense, we can see the richness of Machado de Assis chronicles, often left on the sidelines in favor of his short stories and romances. In addition, the dialogue, to rewrite the epic in his chronicle, Machado seems to contribute to this "continuous creation", reviving the memory of literature and emphasizing the permanence of classical work.